The Depiction of Lung Function and Fractional-Exhaled Nitric Oxide (FeNO) among Asthmatic Outpatients: A Preliminary Study - Mulkan Azhary; Ratnawati Ratnawati; Budhi Antariksa (Jurnal Respirologi Indonesia, 2021)
Background: Asthma is a heterogeneous disease manifested by airway inflammation and wheezing, dyspnea, breathlessness and cough which are varied in intensity and time accompanied with variably restricted expiratory airflow. Asthma patients experienced decreased lung function that occured during asthma attack accompanied by increased levels of fractional-exhaled nitric oxide (FeNO) caused by the pathophysiological process of asthma and the resulting ventilation problems. The study aimed to reveal the depiction of lung function using spirometry dan FeNO level among asthmatic outpatients. Methods: This was a cross sectional study involving 13 uncontrolled-moderate persistent asthmatic outpatients at Asthma Clinic of Persahabatan General Hospital during October 2019 – March2020. The involved respondents had to undergo the spirometry test and the measurement of FeNO level. Results: The uncontrolled-moderate persistent asthmatic patients were dominated by female with mean age of 48.38+12.494 years old. The mean predicted FEV1 was 70.38+20.230% of whom 61.54% patients showed moderate obstruction. The mean FEV1/FVC ratio was 72.85+12.681% of whom 53.85% patients showed obstruction inFEV1/FVC ratio. The mean FeNO level was 29.62+9.152 ppb of whom 76.92% patients had FeNO level ranging 25-50 ppb. Conclusion: The moderate persistent asthmatic patients showed a decreased lung function with reduction of FEV1, obstructive FEV1/FVC ratio as well as increasing FeNO level.